Tumor-Derived circRNAs as Circulating Biomarkers for Breast Cancer - Yu, Yunhe; Zheng, Wenfang; Ji, Changle; Wang, Xuehui; Chen, Mingkuan; Hua, Kaiyao; Deng, Xiaochong; Fang, Lin (Frontiers in Pharmacology, 2022)
Early diagnosis is the key to improving the prognosis of breast cancer (BC) patients; however, there are currently no circulating biomarkers with satisfactory sensitivity and specificity. This study found three tumor-derived differentially expressed circRNAs in BC plasma: hsa_circ_0000091, hsa_circ_0067772 and hsa_circ_0000512, using circRNA microarray, screening, and verifying in plasma samples. The diagnostic model was constructed using logistic regression analysis in the training set, and an optimal diagnostic model was established based on the three circRNAs, which showed sensitivity, specificity, and area under the curve (AUC) values of 0.971, 0.902, and 0.974, resprctively. The diagnostic model was verified in the test set and showed satisfactory stability for BC diagnosis. Furthermore, the expression of hsa_circ_0000091 in plasma was correlated with axillary lymph node (ALN) metastasis, TNM stage, and prognosis of BC patients. Hsa_circ_0000091 combined with ultrasound showed predictive ability for ALN metastasis with an AUC of 0.808. In conclusion, the three circRNAs can be used as circulating biomarkers for BC diagnosis. Hsa_circ_0000091 may serve as a prognostic biomarker for BC, and provide a new approach to predict ALN metastasis.